Nurses' knowledge, barriers and practice in the care of patients with delirium in the intensive care unit in Poland—A cross-sectional study - Lange, Sandra; Mȩdrzycka-Da̧browska, Wioletta; Tomaszek, Lucyna; Wujtewicz, Magdalena; Krupa, Sabina (Frontiers in Public Health, 2023)
Background Delirium is a cognitive disorder that occurs with high frequency in patients in intensive care units and affects patient outcomes. Despite recommendations for monitoring and assessing delirium in the ICU, studies show that it is still not routinely assessed and often remains undiagnosed or misinterpreted as dementia or depression. Aim The aim of this study was (1) to assess nurses' knowledge and clinical practices regarding delirium, (2) to identify the factors associated with nurses' knowledge, and (3) to define barriers to effective control of delirium. Methods A cross-sectional study was conducted among 371 ICU nurses in Poland. Results 53.1% of nurses had never been educated on delirium control resulting in a deficit in knowledge of delirium symptoms, risk factors and complications associated with delirium in ICU patients. Master's degree in nursing (vs. Registered nurses + Bachelor's), female gender, and working in university hospital (vs. other) were positively correlated with nurse's knowledge, while age had a negative impact on knowledge. Delirium is a marginalized state in ICU patients, only 16.4% of nurses assessed delirium routinely and 35.8% assessed delirium occasionally, rarely using validated scales. Barriers to effective delirium control were primarily the lack of a requirement to assess delirium, the difficulty of assessing delirium in intubated patients and nurses' lack of confidence in their ability to use delirium assessment tools. Conclusions There is an urgent need to educate nurses about delirium and to make delirium assessment obligatory in clinical practice. The area of change should also include a hospital policy on delirium monitoring and management. The study was registered on ClinicalTrials.gov (NCT05384964).